X-ray diffraction of concrete composites of high structural strength and density - Sumariuk, Oleksandr; Fodchuk, Ihor; Romankevych, Volodymyr (Physics and Chemistry of Solid State, 2021)
Аn analysis of the structure formation of concrete composites, compressive strength of which exceeds 120 MPa and a quantitative analysis of their qualitative composition and hydration products by X-ray diffraction, x-ray spectral analysis. The main factors affecting the physicomechanical parameters of the complex of various nanofillers and the formation of a denser cement stone structure, which mainly includes calcium hydrosilicates, calcium silicate hydroaluminates and hydroaluminates of various basicity, are studied.